Blume-Emery-Griffiths spin glass and inverted tricritical points - Ozcelik, V. Ongun; Berker, A. Nihat (American Physical Society (APS), 2008)
The Blume-Emery-Griffiths spin glass is studied by renormalization-group theory in d=3. The boundary between the ferromagnetic and paramagnetic phases has first-order and two types of second-order segments. This topology includes an inverted tricritical point, first-order transitions replacing second-order transitions as temperature is lowered. The phase diagrams show disconnected spin-glass regions, spin-glass and paramagnetic reentrances, and complete reentrance, where the spin-glass phase replaces the ferromagnet as temperature is lowered for all chemical potentials.

Added discussion, references, and figure insets. 5 pages, 6 figures. Published version
Keywords: Statistical Mechanics (cond-mat.stat-mech); Condensation; Physics; Systems; FOS: Physical sciences; Dimensions; Disordered Systems and Neural Networks (cond-mat.dis-nn); Condensed Matter - Disordered Systems and Neural Networks; Lattice-gas model; st-order phase-transitions; Renormalization-group; Hierarchical lattices; Ising-model; Systems; Condensation; Dimensions; Separation; Disorder; Hierarchical lattices; Separation; st-order phase-transitions; Mathematical physics; Ising-model; Disorder; Renormalization-group; Physics; Mathematical physics; Lattice-gas model; Condensed Matter - Statistical Mechanics